Polymer-derived Ceramics as Innovative Oxidation Barrier Coatings for Mo-Si-B Alloys. Issue 1760 (2nd February 2015) - Krüger, Manja; Hasemann, Georg; Baumann, Torben; Dieck, Sebastian; Rannabauer, Stefan
ABSTRACT: Three phase Mo-Mo3 Si-Mo5 SiB2 alloys possess excellent mechanical properties over a wide temperature range. The Mo solid solution phase is needed for balanced mechanical properties at room temperature. However, this phase suffers from catastrophic oxidation behavior at high temperatures caused by the formation and evaporation of MoO3 . The oxidation resistance of three phase alloys benefits from a high volume fraction of intermetallic phases. In particular Mo5 SiB2 leads to the formation of a borosilicate protective glassy layer on the material's surface while exposed to air at elevated temperatures. Hence, it is unlikely to identify alloy compositions that will yield both optimum mechanical and oxidation performance. Different coating systems and techniques, such as pack cementation, magnetron sputtering and plasma spraying are discussed in the literature to control the oxidation properties of Mo-based alloys. A different approach is to apply coating systems based on polymer derived ceramics (PDCs). Our present work introduces PDCs as a new type of promising and innovative oxidation-protective coatings for high temperature Mo-based alloys. After dip-coating with perhydropolysilazane (PHPS) and pyrolysis at 800 °C, dense and well-adhered SiNO ceramic layers could be achieved. These were investigated by scanning electron microscopy. Cyclic oxidation tests at 800 °C and 1100 °C were performed to investigate mass changes due to the thermal treatment. Indeed, even thin pyrolyzed PHPS layers with a thickness of around 70 nm to 175 nm protected the Mo-Si-B substrate during the initial stage of oxidation. By increasing the silicon oxide concentration at the material's surface a first oxidation barrier was provided and thus, the strong initial mass loss could be decreased as compared to uncoated alloys. Furthermore, first results of the ongoing optimization process on PDC-coatings applied to Mo-Si-B alloys will be presented, involving the enhancement of the coating´s thickness or varying pyrolysis atmospheres.